Kuasa Atas Perempuan dalam Novel Yaumiyyātu Rūza Karya Rīm Al-Kamāli: Analisis Relasi Kuasa Michel Foucault - Fadhilah, Hanifah Nur (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
Women within cultural contexts, including Arab culture, become real subjects who experience power. This power is exercised not only repressively, but also productively, moving subtly within human relations that are not only found in the empirical world but also in the literary world. Arising from this issue, this study examines the power over women in Arab culture through the novel Yaumiyyātu Rūza by Rīm al-Kamālī as a reflection of the traditional society's social life in the United Arab Emirates in the 1960.This research aims to reveal the forms of power over women's bodies and minds as well as the resistance that arises from this power by using Michel Foucault's theory of power relations. The main data source of this research is the novel Yaumiyyātu Rūza by Rīm al-Kamālī, and the method used is a descriptive qualitative method. The results show that power operates over the body and mind through three main mechanisms: discipline of body and behavior, which commands women to physical and social norms, control of discourse and knowledge, which limits women's access to education and social relations, and normalization of identity, which makes women internalize dominant roles and discourses voluntarily. The resistance that emerges is in the form of subtle resistance carried out by female characters through writing, emotional outbursts, and other symbolic actions. The resistance reflects that women are not merely objects of power, but also agents who are able to reshape their subjectivity in the midst of power networks.